Corruption, workers remittances, FDI and economic growth in five South and South East Asian countries: A panel data approach - Azam, Muhammad; Hassan, Sallahuddin; Khairuzzaman (IDOSI Publications, 2013)
This study attempted to examine the impacts of corruption, foreign direct investment (FDI) and workers remittances on economic growth in a set of five South and South East Asian countries during the period ranging from 1985 to 2011.By using of panel data, fixed effects and random effects models, the study obtained evidence of the positive and statistically significant effects of FDI and workers remittances on economic growth. Empirical results also show negative and statistically significant impact of endemic corruption on economic growth during the study period.